Mechanical control of Eryngium horridum ("Caraguatá") in a grassland of Entre Ríos, Argentina - Lallana, V. H.; Elizalde, J. H. I.; Billard, C.; Lallana, M. del C. (Agrociencia Uruguay, 2006)
Eryngium horridum (Malme) is a native, thorny and aggressive species found in most of Entre Rios (Argentina) natural grassland and in the Oriental Republic of Uruguay. Its invasion is produced in an irregular way, making groups which reduce significantly the actual pasturage surface and competing with forage species for water, light and nutrients. Its control is difficult because it is a plant that reproduces by seed and also vegetatively by rhizome sprouting from which 4 shoots per plant can develop. Partial results have been obtained as regards control through fire, pasturage, chemical or mechanical control. The objective of this work is to evaluate soil laboring, done in autumn and spring during a year on Eryngium horridum control and on grassland specific composition and coverage. The work was done using offset disk harrow, 10 to 15cm of depth. Treatments were T1, one pass; T2, double pass; and T3 no work (control). Treatment T1, carried out in fall, was controlled the “caraguata” with less disturbance and pasture weeding.